Some features in experimental determination of subcriticality in nuclear reactor and accelerator driven system - V. I. Borysenko; I. M. Kadenko (Ядерна фізика та енергетика)
Article is dedicated to the analysis of some terms and definitions of the normative document "General safety provisions for subcritical nuclear installation". The main attention is given to the discussion of such terms as effective multiplication factor, self-sustaining fission chain reaction, subcritical nuclear installation. For correct definition of these terms there should be considered the reactor kinetics equations, from which it follows that the stationary neutron flux can be realized both in the critical and subcritical reactor. Meanwhile, definitions in the corresponding normative document take into account only the critical state of the reactor, whereas other stationary states in "subcritical state" were not properly considered. It is offered "to clarify" corresponding definitions of these terms based on the analysis of nuclear reactor kinetics equations.